2018
DOI: 10.1002/elan.201800146
|View full text |Cite
|
Sign up to set email alerts
|

One‐pot Electro‐polymerized SDPAS/PPy/CNTs Modified Electrode for Selective Detection of Dopamine

Abstract: To improve the performance of dopamine (DA) detection in the presence of ascorbic acid (AA) and uric acid (UA), sodium diphenylamine sulfonate/polypyrrole/multi‐walled carbon nanotubes (SDPAS/PPy/CNTs) film was fabricated on the surface of gold electrode through one‐pot polymerization initiated by electrochemical oxidation. SDPAS were covalently embedded into the backbone of PPy to endow the resultant film with numerous negative‐charged terminals, resulting in selective pre‐adsorption of protonated DA+ on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…We found that Au NP functionalization much improved the linearity from 75 nM compared with the CNT layer itself (450 nM). The liquid metal-based DA sensors exhibited a sensitivity of 0.236 ± 0.013 μA/μM and an LOD of 23.2 nM ( S / N = 3); those values are competitive compared to those of other carbon and gold nanostructures on mechanically rigid platforms that are tabulated in Table . ,, ,, All CV curves with DA concentrations to obtain the anodic peaks are shown in Figure S8.…”
Section: Resultsmentioning
confidence: 99%
“…We found that Au NP functionalization much improved the linearity from 75 nM compared with the CNT layer itself (450 nM). The liquid metal-based DA sensors exhibited a sensitivity of 0.236 ± 0.013 μA/μM and an LOD of 23.2 nM ( S / N = 3); those values are competitive compared to those of other carbon and gold nanostructures on mechanically rigid platforms that are tabulated in Table . ,, ,, All CV curves with DA concentrations to obtain the anodic peaks are shown in Figure S8.…”
Section: Resultsmentioning
confidence: 99%
“…The PDA@CNTs–PEDOT-coated electrode exhibited a good selectivity for electrochemical detection of DA in the presence of UA, AA, and Tryp. The sensitivity was found to be 7.35 μA/M, and the detection limit was 0.62 μm/L, which was better than the other PEDOT-based electrodes reported previously. , Increased sensor activity might be due to the electrostatic interaction between the negatively PDA@CNTs present in PDA@CNTs–PEDOT composite and positively charged DA . In addition, the PDA@CNTs–PEDOT sensor was applied for detection of DA in the human serum sample.…”
Section: Resultsmentioning
confidence: 73%
“…A typical XPS survey spectrum for a Pd 36 ‐Ni 7 /Cd 57 /PPy/Ti electrode is displayed in Figure A, which further confirms the existence of C, O, Pd, Ni, and Cd elements in the film. The C1s spectrum (Figure B) exhibits two peaks, which are assigned to the C―C/C = C (284.7 eV) bands and the C―N bond (285.6 eV) in the PPy ring, respectively . Figure C depicts the binding energies located at 404.8 eV (Cd 3d5/2) and 411.6 eV (Cd 3d3/2), which are attributed to the presence of metallic cadmium Cd(0) .…”
Section: Resultsmentioning
confidence: 99%
“…The C1s spectrum ( Figure 7B) exhibits two peaks, which are assigned to the C-C/C = C (284.7 eV) bands and the C-N bond (285.6 eV) in the PPy ring, respectively. 43,44 Figure 7C depicts the binding energies located at 404.8 eV (Cd 3d5/2) and 411.6 eV (Cd 3d3/2), which are attributed to the presence of metallic cadmium Cd(0). 45 The content of Cd (II) was too small to be detected by XPS.…”
Section: Xps Analysismentioning
confidence: 99%